Measuring maternal near-miss in a middle-income country: assessing the use of WHO and sub-Saharan Africa maternal near-miss criteria in Namibia - Steffie Heemelaar; Leonard Kabongo; Taati Ithindi; Christian Luboya; Fidelis Munetsi; Ann-Kathrin Bauer; Amelie Dammann; Anna Drewes; Jelle Stekelenburg; Thomas van den Akker; Shonag Mackenzie (Taylor & Francis Group, 2019)
Background: Namibia, a middle-income country in sub-Saharan Africa (SSA), plans to use the Maternal Near Miss (MNM) approach. Adaptations of the World Health Organization (WHO) MNM defining criteria ('WHO MNM criteria') were previously proposed for low-income settings in sub-Saharan Africa ('SSA MNM criteria'), but whether these adaptations are required in middle-income settings is unknown. Objective: To establish MNM criteria suitable for use in Namibia, a middle-income country in SSA. Methods: Cross-sectional study from 1 March 2018 to 31 May 2018 in four Namibian hospitals. Pregnant women or within 42 days of termination of pregnancy or birth, fulfilling at least one WHO or SSA MNM criterion were included. Records of women identified by either only WHO criteria or only SSA criteria were assessed in detail. Results: 194 Women fulfilled any MNM criterion. WHO criteria identified 61 MNM, the SSA criteria 184 MNM. Of women who only fulfilled any of the unique SSA MNM criteria, 18 fulfilled the criterion 'eclampsia', one 'uterine rupture' and five 'laparotomy'. These women were assessed to be MNM. Thresholds for blood transfusion to define MNM due to haemorrhage were two units in the SSA and five in WHO set. Two or three units were given to 95 women for mild/moderate haemorrhage or chronic anaemia who did not fulfil any WHO criterion and were not considered MNM. Fourteen women who were assessed to be MNM from severe haemorrhage received four units. Conclusions: WHO MNM criteria may underestimate and SSA MNM criteria overestimate the prevalence of MNM in a middle-income country such as Namibia, where MNM criteria 'in between' may be more appropriate. Namibia opts to apply a modification of the WHO criteria, including eclampsia, uterine rupture, laparotomy and a lower threshold of four units of blood to define MNM. We recommend that other middle-income countries validate our criteria for their setting.